2009
DOI: 10.19041/apstract/2009/3-4/7
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of accounting and management accounting during economic downturns

Abstract: Economic slowdown and downturn creates new situation for every organisation, no one can avoid facing to new situation created by the global financial-, and economic crisis.All of the organisational function should reconsider its own role within the company due to the new circumstances, Accounting and Mangement Accounting can not be exception, but they have more complex and emphasized role in these difficult times. In the following paper I can not avoid to mention some general statement about importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is consistent with the results of Pavlatos and Kostakis [5] who demonstrated that those budgeting tools which allowed tighter control, such as budgeting for controlling costs, gained in importance and use during the crisis, and the findings of Hyvonen [106] who considered budgeting techniques as important and widely used by management in cost controlling and planning in the times of progressing economic decline. Dekan [1] also concluded that in the times of economic recession, the companies tended to reduce spending in any discretionary areas to lessen existing cash-flow needs, as well as handled indirect cost during falling production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is consistent with the results of Pavlatos and Kostakis [5] who demonstrated that those budgeting tools which allowed tighter control, such as budgeting for controlling costs, gained in importance and use during the crisis, and the findings of Hyvonen [106] who considered budgeting techniques as important and widely used by management in cost controlling and planning in the times of progressing economic decline. Dekan [1] also concluded that in the times of economic recession, the companies tended to reduce spending in any discretionary areas to lessen existing cash-flow needs, as well as handled indirect cost during falling production.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, the global economic environment has become increasingly volatile. Instability affects all countries, all sectors, and all types of businesses [1]. In such conditions, the ability of an organization to anticipate and respond to external fluctuations is critical for its survival [2].…”
Section: Introductionmentioning
confidence: 99%
“…The global economic environment, which has become increasingly volatile in recent years, has affected the ability of organizations to adapt to the conditions to survive in the context of a growing demand for sustainability [1,[6][7][8]. Managerial accounting can be the answer through which the accounting and reporting of the sustainability of organizations can be organized effectively, using new digital technologies that have generated a digital transformation of business models.…”
Section: Literature Reviewmentioning
confidence: 99%